Use of feeding jejunostomy in a type IV jejuno-ileal atresia in a low-income country - Patrick Charlorin; Osnel Louima; Gabriel Steve Pierre; Roberto Peigne; Alexis Bowder; Andriani Grazia Maria; Augustin Sylvio (Elsevier, 2020)
Intestinal atresia is a rarely reported congenital anomaly in Haiti. To date there exists little to no published data describing the management of this entity in Haiti. As a low-income country, diagnosis and management of intestinal atresia is a big challenge due to limited resources and limited access to pediatric surgery centers. The purpose of this case report is to describe successful management of a type IV jejunoileal atresia in Haiti. We present a case of a type four intestinal atresia associated with malrotation. Even with a prenatal ultrasound and postnatal plain films concerning for gastrointestinal obstruction, surgery was not performed until seventeen days of life. The clinical course was marked by malnutrition and sepsis. However, the outcome after surgery was good, aided by early enteral feeding through a jejunostomy tube and peripheral parenteral nutrition. Management of intestinal atresia is a large challenge in low-income countries like Haiti. However, acceptable outcomes can be achieved by adapting the surgical technique to permit an early introduction of enteral nutrition.